KONSEP CORPORATE SOCIAL RESPONSIBILITY DALAM PERSPEKTIF KONVENSIONAL DAN FIQH SOSIAL - Santoso, Sugeng (IAIN Tulungagung, 2016)
The term”corporate social responsibility” (CSR) was firstlyintroduced in 1960 when A.B. Carrol addressed H.R. Bowen, the writerof a book entitled “Social Responsibilities of the Businessman” as thefounding father of CSR. Since then, the theory of CSR has evolved forabout five decades and been implemented by a number of corporatein many countries including Indonesia. Although CSR was developedfrom the Western perspectives, it turns out that it is matched with theIslamic perspectives. This paper discusses the concept of CSR fromthe Islamic perspectives and its implementation in business. The fourprinciples of Islamic ethics, -unity, economic freedom, balance, andresponsibility- might be developed into more descriptive principles sothat they can be applied as the Islamic social and economic system. Theultimate goal of the Islamic social and economic system is to preservethe shariah (maqasid al shariah), respect the individuals, preservethe freedom of thinking, preserve the generation, and preserve theproperties to achieve the prosperous and wealthy society.Kata kunci: Corporate Social Responsibility, Konvensional, FiqhSosial